Quand le récit de soi révèle la fonction élucidante de l’écriture - Anne Strasser (Temporalités)
Some contemporary authors choose to tell about their life or part of it in an original way, leaving aside traditional autobiographies as well as the more recent auto-fiction. Such originality may result in disconcerting speech patterns (Annie Ernaux, Les Années, Michel Rostain, Le Fils, Régis Jauffret, Lacrimosa, Daniel Pennac, Le Journal d’un corps) and/or in having the fact of writing itself become part of the text: the author tells about his/her past existence and at the same time about the tale we are reading (Les Années, Delphine de Vigan, Rien ne s’oppose à la nuit). As a consequence, that unexpected narrative reflects a specific connections between the past being told and the present act of writing, for while traditional autobiographies allowed a clear separation between time told and time of telling, we realize how much the past is actually written with an eye to the present. This mise en abîme of the act of writing shows that it is part of the quest for identity which lies at the heart of all autobiographical narratives. Authors are searching for a form allowing them to get as close as possible to their own truth or at least try to approach it, and they are accounting for that search.